Multimodal imaging study of hepatic perivascular epithelioid cell tumors: a case report - Yang, Wenbi; Sun, Quanlin; Shang, Maocai; Li, Song; Hu, Xiao; Hu, Xianwen (Frontiers in Medicine, 2023)
Hepatic perivascular epithelioid cell tumors (PEComas) are rare interstitial tumors that are often misdiagnosed as hepatocellular carcinomas due to their unique vascular enhancement patterns. Herein, we present a case of a 61-year-old man who was incidentally found to have a lesion in the left medial segment of the liver during a chest computed tomography (CT) examination performed 4 days prior to his presentation for chest discomfort. Imaging revealed solid components with density similar to that of normal liver tissue and areas of low-density adipose tissue within the lesion. The solid components exhibited increased uptake of fluorine-18 fluorodeoxyglucose on positron emission tomography/CT. Magnetic resonance imaging demonstrated areas with unevenly high signal intensity in both T1-weighted imaging (T1WI) in-phase and T2-weighted imaging (T2WI) sequences, while T2WI in the opposite phase displayed areas with unevenly low signal intensity, indicating the presence of fatty components. Contrast-enhanced T1WI displayed a “fast in and fast out” enhancement pattern. These distinct imaging features contribute to the diagnosis of hepatic PEComas and distinguish it from hepatocellular carcinoma.